KEPUTUSAN BELANJA ONLINE DIKALANGAN MAHASISWA SAAT PANDEMI COVID -19 (STUDI PADA MAHASISWA SEKOLAH TINGGI MANAJEMEN INFORMATIKA DAN KOMPUTER GICI) - Sahara Sahara; Rudi Yanto Batara Silalahi (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2020)
The purpose of this study is to determine the personal and psychological influence of STMIK GICI students either partially or simultaneously on their decision in shopping online. The sampling technique using purposive sampling of 50 STMIK GICI students as samples, to be analyzed then proccess the hypothesis testing. The results of this study are 1) there is a significant personal influence sig 0.000 <0.05 on online shopping decisions, 2) there is a significant psychological influence sig 0.000 on online shopping decisions, and 3) simultaneously personal and psychological have a significant influence sig 0.000 <0 , 05 on the decision to shop online in STMIK GICI students.